Gut microbiota mediated the toxicity of high concentration of dietary nitrite in C57BL/6 mice - Xu, Jing; Wang, Mingzhu; Liu, Qiuping; Lin, Xiaoying; Pu, Kefeng; He, Zhixing (Ecotoxicology and environmental safety, 2022)
Growing evidence indicates that exposure to high levels of nitrite for a prolonged time has adverse health effects. Although gut microbiota is responsible for the transformation of nitrite in the gut, the evidence concerning whether gut microbiota mediates the toxicity of nitrite is still lacking. The present study addressed the long-term effects of dietary nitrite on male C57BL/6 mice and employed fecal microbiota transplantation (FMT) to reveal whether gut microbiota mediated the effects of nitrite. Furthermore, the effect of azoxymethane (AOM) on gut microbiota was detected for mice drinking normal or nitrite-containing water. High nitrite had toxic effects on C57BL/6 mice. Meanwhile, high nitrite induced skin lesions in mice, accompanied with increased serum ALT, colon IL-6, TNF-α, and MDA levels, together with decreased serum Cr, colon sIgA, and T-AOC levels. After fecal microbiota was transplanted into the normal mice, the nitrite-regulated gut microbiota could also induce skin lesions, coupled with reduced serum Cr, and increased colon MDA. The high dose of nitrite caused the upregulations of Alistipes, Prevotella, and Ruminococcus, which could be transplanted into normal mice through FMT. Inversely, gut microbiota from normal mice reduced the effects of nitrite on serum ALT and Cr, together with colon sIgA and MDA. Gut microbiota from normal mice could also upregulate metabolic genes and downregulate stress genes in the nitrite-treated mice. It might due to the upregulation of Akkermansia and Parabacteroides caused by FMT from normal water-treated mice to nitrite-treated mice. In addition, AOM exhibited to be more toxic to the colon in the nitrite-treated mice in comparison with normal water-treated mice, and it might be due to the expression of Hspa1a and Hspa1b in the colon. Interestingly, gut microbiota was more influenced by AOM in the normal water-treated mice than the nitrite-treated mice. Overall, these data demonstrated that gut microbiota mediated the toxicity of a high concentration of dietary nitrite. [Display omitted] •Long term of nitrite (0.3 g/L NaNO2 in drinking water) caused toxicity on C57BL/6 mice.•The toxicity of nitrite could be alleviated by the transplantation of fecal microbiota from normal C57BL/6 mice.•The gut microbiota regulated by nitrite could induced the toxicity as the nitrite in C57BL/6 mice.•Azoxymethane (AOM) exhibited to be more toxic to colon in the nitrite-treated mice than in the normal water-treated mice.